Training on the Development of Digital-Based Learning Media (Canva for Education) for Chemistry Teachers of MGMP Kabupaten Solok in order to support the implementation of the Merdeka Curriculum - Fitri, Bali Yana; Aini, Faizah Qurrata; Kurnia, Reni; Yerimadesi, Yerimadesi; Desyafrianti, Vanny; Rindiany, Nindy Aprillia (Fakultas MIPA Universitas Negeri Padang, 2024)
The change in the current curriculum, from the 2013 curriculum to an merdeka curriculum, creates obstacles for MGMP teachers in preparing the scope of material that must be delivered to students in order to achieve curriculum goals. Apart from that, the incomplete scope of the material will result in the teacher's availability of digital-based learning media not being met, even though there are already platforms that can support the development of learning media.Therefore, training in the development of digital-based learning media (Canva for Education) is needed for Solok Regency Chemistry MGMP chemistry teachers in order to support the implementation of the independent curriculum. Based on the training activities that have been carried out, it can be concluded that this activity is useful for increasing teacher competence in developing digital learning media